Współczesna teatrologia – pomiędzy średniowieczem a modernizmem - Bering, Piotr (Litteraria Copernicana, 2008)
The article is an attempt of bringing closer to dilemmas of the modern theatre studies, taking the studies on medieval theatre under particular consideration. Both the results of work of XII Congress Société internationale pour l’étude du théâtre médiéval (July 2007) and the books written and coedited by Christopher Balme indicate that between the me - dieval theatre and a part of modern theatrical stagings, especially paratheatrical ones, numerous similarities occur. It is a result of moving the centre of gravity from an aesthetic sphere to the sphere of interpersonal communication. Therefore rituals, protests etc. become a subject of interest of many theatrologists again, whereas the researchers of medieval theatre have been analyzing the phenomena on the border of theatricality since a long time ago. Moreover some of elaborated research tools can be applied both to the modern theatre and to the preromantic theatre. In particular the research techniques serving an analysis of performativity seem to be very universal tools that are applicable to different epochs and different spheres of social life.